A framework for an in-house development of educational management information system. (2012)
"A large percentage of Nigerian educational institutions use manual and paperbased system for collecting, processing, and disseminating information. This approach results in inefficient utilization of resources, low productivity and stunted growth of the educational sector. In this study the in-house users-development approach has been used to develop a computer based Educational Information Management System (ElMS) for a typical University academic department. The existing work system and the underlying Information flow pattern in a department were critically studied. The associated information needs were identified and analyzed. A broad review of the literature on Information Technology (IT) solutions were carried out to identify possible solutions frame work. Graphical User Interface (GUI) software embedded in Relational Database Management System (RDBMS), Microsoft Access was developed using Visual Basic Net. The software was deployed and tested using data from the department of Industrial Engineering, University of Ibadan. The GUI, compatible with the regular Windows environment, was shown to be user friendly. The capability of the EIS compares very well with the imported EIS systems. "